Electric-field control of ferromagnetism in a Co-Fe-Ta-B amorphous alloy. (5th April 2018) - Zhang, Yingqi; Zhao, Shaofan; Song, Cheng; Liu, Wenjian; Yao, Kefu; Chen, Na
Abstract: We report the formation of a ferromagnetic Co55.0 Fe24.5 Ta0.1 B20.4 amorphous alloy by magnetron sputtering, which exhibits positive magnetoresistance without saturation even in very high magnetic fields. This suggests that the s -like electrons responsible for the electrical conduction are spin-polarized through s - d hybridization. Owing to the electromagnetic interplay of the spin-polarized conduction electrons with the local magnetic moments, the electric-field control of room-temperature ferromagnetism is realized in the amorphous alloy. Our results offer insights for exploring the multi-functionalities of ferromagnetic amorphous alloys and extending their applications to a wide variety of electronics including magnetic tunnel junctions and compact disks. Graphical abstract: Highlights: Electric-field control of the room-temperature ferromagnetism has been realized in a ferromagnetic amorphous alloy. At high magnetic fields, the amorphous ferromagnet exhibits positive magnetoresistance with weak temperature dependence. The spin-polarized conduction electrons cause the electric-field control of ferromagnetism and positive magnetoresistance.